Improving The Results Of Treatment Of Locally Advanced Oropharyngeal Cancer With The Study Of Epidemiological And Molecular Biological Features (Literature review) (Eurasian Medical Research Periodical, 2024)
To provide data on improving the results of treatment of locally advanced oropharyngeal cancer, taking into account epidemiological and molecular biological characteristics.